PREDIABETES PATIENTS WITH ACUTE CORONARY SYNDROME AND HOSPITAL CLINICAL OUTCOME - ABDULLAHAL-SHORBAGY, EMAN; IBRAHIM, GEHANABDEL–KADER; SAAD, MOHAMED S. S.; HARSHA, KHALED BASHIR SALEM (The journal of contemporary issues in business and government, 2021)
BACKGROUND: PREDIABETES IS COMMON IN PATIENTS PRESENTING WITH ACS WHO ARE NOT PREVIOUSLY KNOWN TO HAVE DIABETES. PREDIABETIC PATIENTS HAD WORSE IN-HOSPITAL CLINICAL OUTCOMES COMPARED WITH PATIENTS WITHOUT DIABETES. THE AIM OF THE STUDY WAS TO EXPLORE THE RELATION PREDIABETES PATIENTS WITH ACUTE CORONARY SYNDROMES THE IN-HOSPITAL CLINICAL OUTCOMES. PATIENTS AND METHODS: THIS PROSPECTIVE STUDY WAS CONDUCTED ON 60 PATIENTS WITH ACUTE CORONARY SYNDROME WHO ADMITTED TO THE INTENSIVE CARE UNIT (ICU), INTERNAL MEDICINE DEPARTMENT, FACULTY OF MEDICINE, ZAGAZIG UNIVERSITY DURING THE PERIOD FROM SEPTEMBER 2019 TO MARCH 2020. ALL STUDIED SUBJECTS WERE SUBJECTED TO FULL HISTORY TAKING COMPLETE CLINICAL EXAMINATION, COMPLETE BLOOD COUNT, GLYCOSYLATED HAEMOGLOBIN (HBA1C), LIPID PROFILE, SERUM CREATININE AND ORAL GLUCOSE TOLERANCE TEST (OGTT), ECG AND ECHO. RESULTS: THERE WAS A STATISTICAL SIGNIFICANT DIFFERENCE BETWEEN THE STUDIED GROUPS REGARDING ACUTE CORONARY SYNDROME TYPES, GLYCATED HAEMOGLOBIN (HBA1C), SERUM CREATININE, AND HIGH-DENSITY LIPOPROTEINS. CHOLESTEROL. THERE WAS STATISTICALLY SIGNIFICANT DIFFERENCE BETWEEN THE STUDIED PATIENTS GROUPED ACCORDING TO THE CLINICAL OUTCOME REGARDING ACS TYPES. CONCLUSION: PRE-DIABETIC PATIENTS HAD WORSE IN-HOSPITAL CLINICAL OUTCOMES COMPARED WITH PATIENTS WITHOUT DIABETES. PRE-DIABETIC PATIENTS WITH ACS HAVE GREATER PREVALENCE OF CARDIOMETABOLIC RISK FACTORS (ABDOMINAL OBESITY, AND HYPERTENSION) AS COMPARED TO NON-DIABETIC PATIENTS.